Titan's curse the graphic novel - Riordan, Rick; Venditti, Robert; Futaki, Attila; Riordan, Rick (New York Disney*Hyperion Books, 2013)
When the goddess Artemis disappears while hunting a rare, ancient monster, a group of her followers joins Percy and his friends in an attempt to find and rescue her before the winter solstice, when her influence is needed to sway the Olympian Council regarding the war with the Titans.
"Adapted from the novel Percy Jackson & the Olympians, Book Three: The Titan's Curse "--Last page of book
GN370L
Decoding: 5 (very hard) Vocabulary: 5 (very hard) Sentences: 3 (medium) Patterns: 5 (very hard)
Accelerated Reader AR
111818
Keywords: Jackson, Percy -- (Fictitious character) -- Comic books, strips, etc; Artemis -- (Greek deity) -- Comic books, strips, etc; Riordan, Rick -- Adaptations -- Comic books, strips, etc; Mythology, Greek -- Comic books, strips, etc; Animals, Mythical -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Titans (Mythology) -- Comic books, strips, etc; Mythology, Greek -- Fiction; Juvenile Fiction -- Action & Adventure; Juvenile Fiction -- Comics & Graphic Novels; Juvenile Fiction -- Legends, Myths, Fables -- Greek & Roman; Fantasy comic books, strips, etc; Graphic novels; Fantasy comics; Comics (Graphic works); Young adult works